Increase of aqueous inflammatory factors in macular edema with branch retinal vein occlusion: a case control study - Noma Hidetaka; Funatsu Hideharu; Mimura Tatsuya; Shimada Katsunori (BMC, 2010)
Abstract Background This study investigated whether soluble intercellular adhesion molecule-1 (sICAM-1) has a role in the pathogenesis of macular edema associated with branch retinal vein occlusion (BRVO) together with vascular endothelial growth factor (VEGF). Methods A retrospective case control study was performed in 22 patients with BRVO and macular edema, as well as 10 patients with nonischemic ocular diseases as the control group. Retinal ischemia was evaluated by measuring the area of capillary non-perfusion with Scion Image software, while the severity of macular edema was examined by optical coherence tomography. Aqueous humor samples were obtained during the performance of combined vitrectomy and cataract surgery. sICAM-1 and VEGF levels in aqueous humor and plasma specimens were determined by enzyme-linked immunosorbent assay. Results Aqueous humor levels of sICAM-1 (median: 6.90 ng/ml) and VEGF (median: 169 pg/ml) were significantly elevated in BRVO patients compared with the control group (median: 3.30 pg/ml and 15.6 pg/ml, respectively) (P = 0.005 and P < 0.001, respectively). The aqueous humor level of sICAM-1 was significantly correlated with that of VEGF (P = 0.025). In addition, aqueous levels of both sICAM-1 and VEGF were correlated with the size of the non-perfused area of the retina in BRVO patients (P = 0.021 and P < 0.001, respectively). Furthermore, aqueous levels of sICAM-1 and VEGF were both correlated with the severity of macular edema (P = 0.020 and P = 0.005, respectively). Conclusions Both sICAM-1 and VEGF may be involved in the pathogenesis of macular edema associated with BRVO. Measurement of aqueous humor sICAM-1 levels may be useful for assessment of BRVO patients with macular edema, in addition to measurement of VEGF.